ENHANCING FOREIGN LANGUAGE LEARNING THROUGH ARTIFICIAL INTELLIGENCE AND INTEGRATING INTO EDUCATIONAL PROCESS - Kasimova, Malika (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
In the modern educational process, significant attention is paid to the use of artificial intelligence (AI) to enhance the quality of education, especially in the field of foreign language learning. This article explores how the use of AI can increase motivation and engagement among those studying foreign languages. Key components of effective foreign language learning include maintaining a high level of learner activity and combining intrinsic and extrinsic motivation. The study critically analyzes various studies that highlight the capabilities of AI-assisted language learning programs, especially those accessible through computers and smartphones. It emphasizes how these AI tools can be adapted to various learning needs, providing a more personalized and engaging learning experience; focuses on the fundamental psychological and pedagogical principles that underlie motivation in foreign language learning, particularly concentrating on the study of English as an example. Additionally, practical recommendations are offered for educators and students on optimizing the use of AI tools in language education. These recommendations aim to bridge the gap between technology and traditional language teaching methods, offering a more comprehensive and effective approach to language learning.
Keywords: artificial intelligence; Chat GPT; activity; motivation; technology-assisted language learning (TALL)